(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Low utilization of modern contraceptives immediately after birth remains low in Nepal. Hence the Government of Nepal has given significant importance on postpartum family planning to address the unmet need of family planning in Nepal. The aim of the present study was to assess the prevalence of postpartum family planning Utilization among women and its associated factors. MATERIALS AND METHODS: A descriptive, cross- sectional, study was conducted among 133 mothers who had one year of children. The data collection tool was a semi structured interview schedule. Data were entered using Epi data 3.1 software and analyzed using SPSS 16. The statistical analyses carried out were descriptive (frequencies and percentages) and bivariate (chi-square test). RESULTS: The current utilization of family planning methods was 23.3% and utilization of family planning in the past year was 28.6%. The Depo -Provera (38.7%) is the most commonly used family planning method among respondents. About half of the respondents (45.9%) did not get family planning counselling during ANC Visit. Husband Occupation (p-value =0.004), family planning counselling during ANC Visit (p-value =0.017), Knowledge on appropriate birth space (p-value =0.017) and IUCD use (p-value=0.042). CONCLUSIONS: Contraceptive utilization among postpartum mothers was found to be extremely low which ultimately increases health risk to maternal health due to chances of unintended pregnancies.